Fortifying humanitarian supply chains: evaluating sustainability enablers for strengthened resilience of humanitarian supply chains during calamities and pandemics - Vishal Kashav; Chandra Prakash Garg (Journal of Humanitarian Logistics and Supply Chain Management)
Purpose – The purpose of this paper is to identify key sustainability enablers that are crucial for resilient humanitarian supply chains (RHSCs) during natural calamities and pandemics. It also aims to subsequently rank them using the fuzzy analytic hierarchy process (AHP) to assess their importance. The goal is to enhance stakeholders’ understanding, enabling them to implement effective strategies to mitigate disruptions and safeguard RHSCs. Design/methodology/approach – This study applied the fuzzy AHP as part of the multicriteria decision-making (MCDM) framework to prioritize sustainability enablers that are crucial for the resilience of humanitarian supply chains (RHSCs). Findings – The research findings indicate that the operational enablers category is the most critical, followed by the infrastructural and environmental categories, which rank as the second and third most critical, respectively. Among the sub-categories, “Hyper-connectivity,” “Renewable energy sources for infrastructure” and “Sustainable procurement and sourcing practices” are identified as the top three, highlighting the urgency for immediate attention. Research limitations/implications – While this research provides valuable insights, it also presents some limitations and opens new avenues for future study. First, the study predominantly focuses on natural calamities and pandemics, potentially overlooking other catastrophic events that could jeopardize humanitarian supply chains. Second, to eliminate potential biases and develop a more robust model, it would have been beneficial to explore other modern MCDM methods. It is possible that these alternative MCDM techniques might yield better results than fuzzy AHP. Future research could explore a broader range of crises to comprehensively address the varied dynamics influencing Resilient Humanitarian Supply Chains (RHSCs) while also experimenting with different cutting-edge MCDM methods. Additionally, future research could dive deeper into the top-ranked technology enablers, particularly focusing on human-technology interactions within humanitarian supply chains, a topic that is currently being discussed among experts. Social implications – The manuscript emphasizes the importance of global preparedness and collaborative efforts among governments, nongovernmental organizations and communities. Through its discussion of social enablers, this study aims to develop RHSCs that prioritize the well-being of disaster-affected populations and individuals used in this field. Originality/value – This research offers unique insights by ranking sustainability enablers for resilient humanitarian supply chains (RHSCs) amid natural calamities and pandemics, providing novel and actionable contributions.